2019
DOI: 10.1371/journal.ppat.1007840
|View full text |Cite
|
Sign up to set email alerts
|

Natural Immunity to HIV is associated with Low BLyS/BAFF levels and low frequencies of innate marginal zone like CD1c+ B-cells in the genital tract

Abstract: BLyS/BAFF is recognized for its role in B-cell ontogenesis, as well as cell fate decision towards the first-line/innate marginal zone (MZ) B-cell pool. Excess BLyS/BAFF is associated with hyperglobulinemia and increased frequencies of activated precursor-like MZ B-cells. Herein, we show that HIV highly-exposed seronegative (HESN) commercial sex workers (CSWs) had lower soluble BLyS/BAFF levels and relative frequencies of BLyS/BAFF expressing cells in their genital mucosa when compared to those from HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
3
21
1
Order By: Relevance
“…In the female genital tract, the presence of antibodies that are capable of mediating ADCC against HIV gp120 is associated with reduced cervical viral load [59], suggesting that ADCC may act as a mechanism of defense against HIV in this setting. Our finding that NK cells from HESN women have a trend of increased ADCC activity may be particularly relevant as HIV gp41-reactive IgG1 antibodies have been found in CVL samples from women in this cohort [34]. Although no difference in ADCC-mediating antibodies have been observed in this cohort between HESN and healthy women [60], differences in ADCC activity at the level of effector cells could contribute to protection.…”
Section: Plos Onementioning
confidence: 61%
See 1 more Smart Citation
“…In the female genital tract, the presence of antibodies that are capable of mediating ADCC against HIV gp120 is associated with reduced cervical viral load [59], suggesting that ADCC may act as a mechanism of defense against HIV in this setting. Our finding that NK cells from HESN women have a trend of increased ADCC activity may be particularly relevant as HIV gp41-reactive IgG1 antibodies have been found in CVL samples from women in this cohort [34]. Although no difference in ADCC-mediating antibodies have been observed in this cohort between HESN and healthy women [60], differences in ADCC activity at the level of effector cells could contribute to protection.…”
Section: Plos Onementioning
confidence: 61%
“…Prior studies of immune correlates of HIV protection in Beninese HESN women revealed a low inflammatory immune profile in the blood and genital tract. In fact, low levels of soluble B lymphocyte stimulator (BLyS)/BAFF were detected in the blood and cervicovaginal lavages (CVL) [34,35] and low levels of pro-inflammatory cytokines in the CVL of these HESN women [36,37]. This raised the possibility that HIV resistance in these women may be the result of a balance between strong innate immune responses and low inflammatory conditions and fewer HIV target cells at the exposure site [38].…”
Section: Introductionmentioning
confidence: 99%
“…MZB cells are emerging as a cell type of interest in HIV-1 transmission and pathogenesis. Recent studies have reported decreased numbers of MZB in the blood and within the female reproductive tract of HIV-exposed but uninfected commercial sex workers 22,23 . This suggests that MZB cells could be contributing to HIV transmission within the female genital tract, although mucosal B cells at this site are relatively rare 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophages and DCs are more commonly associated with trans infection, there are higher proportions of MZB than macrophages, mDC, or pDC in RM, and it has been shown previously that peripheral B cells mediate trans infection as efficiently as other APC subsets 14 . Although traditional HIV-binding receptors such as CD21 and DC-SIGN were not quantified here, studies have reported MZB cells are capable of binding directly to HIV gp120 23 . When combined with unique intrinsic features of the rectal mucosa ex vivo HIV challenge model (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation